Exploring speaking learning strategies among introverted students in english education programs: A case study - Kuning, Dewi; Elizar, Elizar; Kurniawan, Mirdan (Creative Smart Visionary, 2025)
This study aims to explore the speaking learning strategies employed by introverted students in the English Education program, focusing on how personality traits influence strategic language learning. Employing a qualitative descriptive method, data were collected through semi-structured interviews and questionnaires administered to five fourth-semester students identified as introverts via the Myers-Briggs Type Indicator (MBTI) test. The data were analyzed using thematic analysis through three stages: data reduction, data display, and conclusion drawing. The findings reveal that introverted students predominantly utilize four types of speaking strategies: memory strategies, cognitive strategies, compensatory strategies, and metacognitive strategies. In contrast, affective and social strategies were not employed by the participants, highlighting their preference for introspective and independent learning approaches. Cognitive and compensatory strategies were found to be the most frequently used, indicating a strong inclination toward planning, mental rehearsal, and overcoming limitations in speaking fluency. These results suggest that introverted students benefit from structured, personalized speaking instruction that accommodates their reflective learning styles. The study offers practical implications for educators to design adaptive language learning environments that respect diverse personality traits, thereby enhancing speaking proficiency among introverted learners.